Calidad de los servicios ofertados por la empresa "Caflosa" de la ciudad de Babahoyo periodo 2021. - Caicedo Figueroa, José Andrés (2022)
This case study will focus on investigating the perception of Caflosa's customers in the city of Babahoyo about the quality of the services offered by this company, because with the rapid changes that exist in the world in terms of technological advances, companies competing in the market offering similar services make the tastes and preferences of customers change and this directly affects the use of Caflosa's services today. The realization of this case study is completely justified because according to the results of the investigation, the necessary conclusions and recommendations can be presented to the administrator of the company Caflosa, allowing in some way to make changes that significantly improve a process that directly or indirectly affects the quality of services offered to customers of Caflosa in the city of Babahoyo and its surroundings.